Young Nietzsche and the Wagnerian Experience - Love, Frederick R. (UNC Studies in the Germanic Languages and Literatures, 1963)
Using previously unpublished and neglected sources, this 1963 study of the critical decade in the philosopher's development that culminated in "The Birth of Tragedy" in 1871 fully exploited for the first time the extensive record of Nietzsche's musical compositions and clarifies his traditionally obscure relations to Wagner.